Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
Zygomatic arch fractures are common in craniofacial trauma, but isolated arch fractures are rare and the anatomic determinants of their severity are poorly understood. We examined the relationship between isolated zygomatic arch fractures and maxillary sinus morphology, primarily comparing side-to-side dimensions between the fractured and intact sides and, as a secondary exploratory aim, testing whether intact-side (baseline) morphology was associated with fracture severity. In this retrospective within-patient study, maxillofacial computed tomography from 39 patients with unilateral isolated arch fractures was analyzed. Sinus height, width, and depth were measured on both sides, fractures were graded with the Nam-Jung system, and paired sides were compared using the Wilcoxon signed-rank test. Compared with the intact side, the fractured-side sinus was significantly smaller in height (42.0±6.5 versus 43.5±5.5 mm; P=0.004); depth showed a smaller, nonsignificant reduction in the same direction (39.7±5.8 versus 40.8±5.3 mm; P=0.081); and width did not differ (P=0.23). The reduction was greatest in height (asymmetry index -3.5%) and negligible in width (-1.2%) and remained significant for height in a sensitivity analysis excluding one outlier (P=0.007). Intact-side dimensions did not differ across fracture-severity categories (Kruskal-Wallis P≥0.94), although this comparison was underpowered. Isolated zygomatic arch fractures are therefore associated with a dimension-specific reduction of the maxillary sinus, most robustly in height with width preserved, consistent with inward displacement of the zygomaticomaxillary complex encroaching on the sinus; larger prospective studies are needed for confirmation.